Relationship of scrotal circumference to age, body weight and testicular volume of swamp buffalo - AHMED, K (The Indian Journal of Animal Reproduction, 2023)
Scrotal circumference (SC) and testicular volume (TV) of thirty eight swamp buffalo bulls maintained at LivestockResearch Station, Assam Agricultural University, Mandira and ranging in age from 12 months to 60 months and weighing 132kg to 358 kg. Ages and body weight (BW) were recorded for each male at the time of measurement to find out correlation withSC and TV. SC and TV increased linearly and correlated significantly with age and BW (SC vs age: r=0.72, P
Keywords: scrotal circumference; swamp buffalo